Bcr-Abl tyrosine kinase inhibitors: a patent review. (April 2015) - Desogus, Andrea; Schenone, Silvia; Brullo, Chiara; Tintori, Cristina; Musumeci, Francesca
<x xml:space="preserve">Abstract</x> Introduction: Breakpoint cluster region Abelson (Bcr-Abl) tyrosine kinase (TK) is a constitutively activated cytoplasmic TK and is the underlying cause of chronic myeloid leukemia (CML). To date, imatinib represents the frontline treatment for CML therapy. The development of resistance has prompted the search for novel Bcr-Abl inhibitors. Areas covered: This review presents a short overview of drugs already approved for CML therapy and of the compounds that are in clinical trials. The body of the article deals with Bcr-Abl inhibitors patented since 2008, focusing on their chemical features. Expert opinion: The search for Bcr-Abl inhibitors is very active. We believe that a number of patented compounds could enter clinical trials and some could be approved for CML therapy in the next few years. Overall, Bcr-Abl inhibitors constitute a very appealing research field that can be expected to expand further.